Virtual screening - Van Drie, John H. (Henry Stewart Talks, 2021)
Three methods of virtual screening, Considerations when using virtual screening, Comparing virtual screening to high-throughput screening, Targeting histone acyltransferase (HAT) using virtual screening, Targeting AmpC using virtual screening, Current open questions when using virtual screening